2019
DOI: 10.3389/fnhum.2019.00228
|View full text |Cite
|
Sign up to set email alerts
|

Building Memory Representations for Exemplar-Based Judgment: A Role for Ventral Precuneus

Abstract: The brain networks underlying human multiple-cue judgment , the judgment of a continuous criterion based on multiple cues, have been examined in a few recent studies, and the ventral precuneus has been found to be a key region. Specifically, activation differences in ventral precuneus (as measured with functional magnetic resonance imaging, fMRI) has been linked to an exemplar-based judgment process, where judgments are based on memory for previous similar cases. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 85 publications
(157 reference statements)
0
6
0
Order By: Relevance
“…These instructions may limit the generality of CX-COM as a judgment model. However, the importance of exemplar-based processes in multiple-cue judgments studies without strategy instructions has been frequently demonstrated (Bröder & Gräf, 2018;Hoffmann et al, 2014Hoffmann et al, , 2016Juslin et al, 2008;Karlsson et al, 2007;McDaniel et al, 2018;Stillesjö, Nyberg, & Wirebring, 2019). Furthermore, a thorough, qualitative analysis of previous empirical evidence demonstrates that CX-COM can cover a broader variety of empirical findings (e.g., Juslin et al, 2008), including results that have been taken as evidence for transitions between exemplar memory and cue knowledge.…”
Section: Competitive Retrieval Causes Multimodalitymentioning
confidence: 99%
“…These instructions may limit the generality of CX-COM as a judgment model. However, the importance of exemplar-based processes in multiple-cue judgments studies without strategy instructions has been frequently demonstrated (Bröder & Gräf, 2018;Hoffmann et al, 2014Hoffmann et al, , 2016Juslin et al, 2008;Karlsson et al, 2007;McDaniel et al, 2018;Stillesjö, Nyberg, & Wirebring, 2019). Furthermore, a thorough, qualitative analysis of previous empirical evidence demonstrates that CX-COM can cover a broader variety of empirical findings (e.g., Juslin et al, 2008), including results that have been taken as evidence for transitions between exemplar memory and cue knowledge.…”
Section: Competitive Retrieval Causes Multimodalitymentioning
confidence: 99%
“…Vachon-Presseau et al 94 show parahippocampal gyrus involvement in anticipatory anxiety and associative learning, traits that both determine pain quality experiences. The precuneus cortex is traditionally known to be involved with reflection and episodic memory, 17,82,102 and volumetric studies also show plasticity therein related to chronic pain. 54 Overall, connectivity relating to pain quality was more local than functional connectivity predicting the other pain domains, consistent with the notion that it may be better related to nociceptive characteristics.…”
Section: Pain Domain Relationships To Functional Brain Connectivitymentioning
confidence: 99%
“…This approach is standard in mathematical psychology (Pitt et al, 2002), but can also be done in cognitive neuroscience. For example, Mack and colleagues (Mack et al, 2013) formally evaluated whether the representations in an exemplar or prototype model best matched the BOLD response and found the exemplar model was more consistent (also see Stillesjö et al, 2019). In such cases, brain data can help adjudicate between competing models when behavioural data alone cannot (Ditterich, 2010;Mack et al, 2013;Purcell et al, 2012).…”
Section: Some Functions Of Models In Sciencementioning
confidence: 99%